THE FUNCTIONAL STATE OF STUDENT ORGANIZATIONS AT VARIOUS SCHOOL AGES AND THEIR UNIQUE CHARACTERISTICS (Scientific journal of the Fergana State University, 2025)
This research studies the functional state of students of various school ages and its specific characteristics. The functional state of students' bodies is directly related to their physical and mental development, as well as their success in the educational process. The research analyzes the physiological and psychological characteristics of different age groups, as well as how they respond to changes in the educational environment. Modern methods and tools are used to assess the functional state of students. This work is of significant importance for ensuring the healthy development of students and optimizing the educational process. The results will help in developing educational strategies that take into account the individual characteristics of students.